2012
DOI: 10.1002/adsc.201200036
|View full text |Cite
|
Sign up to set email alerts
|

Europium(III) Triflate‐Catalyzed Trofimov Synthesis of Polyfunctionalized Pyrroles

Abstract: The synthesis of polyfunctionalized pyrroles by reaction of a ketoxime with dimethyl acetylenedicarboxylate using europium(III) triflate as the catalyst is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Amidoximes have been well known to be the useful building blocks for the construction of nitrogen-heterocyclic compounds, and the five-membered nitrogen-heterocyclic compounds formation is usually proposed to involve the step of N-O bond cleavage via 3,3-sigmatropic rearrangement [ 37 , 38 , 39 ]. Therefore, on the basis of our results and the known chemistry of amidoximes, a possible reaction mechanism for the formation of imidazole ring is shown in Scheme 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amidoximes have been well known to be the useful building blocks for the construction of nitrogen-heterocyclic compounds, and the five-membered nitrogen-heterocyclic compounds formation is usually proposed to involve the step of N-O bond cleavage via 3,3-sigmatropic rearrangement [ 37 , 38 , 39 ]. Therefore, on the basis of our results and the known chemistry of amidoximes, a possible reaction mechanism for the formation of imidazole ring is shown in Scheme 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Amidoximes have been well known to be the useful building blocks for the construction of nitrogen-heterocyclic compounds, and the five-membered nitrogen-heterocyclic compounds formation is usually proposed to involve the step of N-O bond cleavage via 3,3-sigmatropic rearrangement [37][38][39]. Therefore, on the basis of our results and the known chemistry of amidoximes, a possible reaction mechanism for the formation of imidazole ring is shown in In order to support the proposed mechanism, a theoretical calculation was conducted by using the quantum chemistry program Gaussian 16 [40], and all structures were optimized by using M06-2X Minnesota functional with the 6-31G(d,p) basis set [41].…”
Section: Ohmentioning
confidence: 99%
“…A variety of classical methods have been reported for the synthesis of pyrroles, such as the Barton-Zard [10], Hantzsch [11], Knorr [12,13], Trofimov [14], Paal-Knorr [15,16], and Clauson-Kaas [17][18][19] reactions and their modifications. In addition, pyrroles have also been synthesized by the Huisgen reaction [20][21][22], cyclization of N-propargylic derivatives [23,24], including propargyl aziridines [25,26], through the cyclocondensation of vinyl azides with 1,3-dicarbonyls [27,28], transition-metal-catalyzed cyclization [29], [3 + 2] cycloadditions [30], and multi-component reactions [4,[31][32][33][34][35][36][37][38][39], among various other alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…16 Among the current most dynamically elaborating methods of the pyrrole synthesis are those based on the rearrangement of available O-vinyl ketoximes which are readily synthesized by addition of ketoximes to acetylenes in the presence of superbases, 17 Au/Ag 18 or Eu(III) catalysts. 19 A breakthrough along this line has been Ir/Ag catalyzed isomerization of allyl ketoximes to their 1-propenyl isomers which further cyclize to pyrroles. 20 In last minute paper, it has been reported that two molecules of O-acylketoximes are transformed (CuBr, DMSO, 140 ºC, 2 h) to tetra-substituted symmetrical pyrroles.…”
Section: Introductionmentioning
confidence: 99%